Clinical case of atypical course of Crohn’s disease - L. V. Zhuravlyova; Yu. K. Sikalo; M. O. Oliinyk; A. K. Zhuravlyova; H. P. Zinchenko; Ye. V. Tytov (Patologìâ)
Crohn’s disease (CD) is a chronic recurrent inflammatory bowel disease with a wide variety of clinical manifestations – from classical gastrointestinal phenotypes to predominance of extraintestinal symptoms. Atypical course of CD is observed relatively often and is manifested with a damage to almost all body systems, including hepatobiliary, immune, hematopoietic, cardiovascular, nervous, as well as eyes, skin, lungs and kidneys. Atypical manifestation often precedes intestinal, making diagnosis difficult. The presence of various clinical manifestations of CD, often an atypical course, as well as the absence of standardized diagnostic criteria can be an obstacle for physicians in the timely detection of the disease and effective treatment.